Pengembangan E-Modul Sebagai Bahan Ajar Bahasa Indonesia Materi Teks Ceramah Kelas XI IPA SMAS Al-Washliyah Pasar Senen - Saputra, Eka; Ali, Ali; Rita, Rita (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aimed to develop and test the feasibility of e-modules as Indonesian language teaching materials for Class XI SMAS in Al-Washliyah Pasar Senen. The research utilized a Research and Development (R&D) approach, following the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation. The sample consisted of 19 students from class XI IPA out of a total population of 45 students. The results indicated that the e-module met the appropriate criteria, with material and design experts validating its content and structure. The teacher evaluation demonstrated a high feasibility level (94%), while students responded positively (92%) to the e-module. Consequently, the findings conclude that the e-module is highly suitable as a teaching material for Class XI SMAS Al-Washliyah.